Red, Green, and Blue Light‐Emitting Polyfluorenes Containing a Dibenzothiophene‐S, S‐Dioxide Unit and Efficient High‐Color‐Rendering‐Index White‐Light‐Emitting Diodes Made Therefrom. (2nd April 2013) - Yu, Lei; Liu, Jie; Hu, Sujun; He, Ruifeng; Yang, Wei; Wu, Hongbin; Peng, Junbiao; Xia, Ruidong; Bradley, Donal D. C.
Abstract A series of blue (B), green (G) and red (R) light‐emitting, 9, 9‐bis(4‐(2‐ethyl‐hexyloxy)phenyl)fluorene (PPF) based polymers containing a dibenzothiophene‐S, S‐dioxide (SO) unit (PPF‐SO polymer), with an additional benzothiadiazole (BT) unit (PPF‐SO‐BT polymer) or a 4, 7‐di(4‐hexylthien‐2‐yl)‐benzothiadiazole (DHTBT) unit (PPF‐SO‐DHTBT polymer) are synthesized. These polymers exhibit high fluorescence yields and good thermal stability. Light‐emitting diodes (LEDs) using PPF‐SO25, PPF‐SO15‐BT1, and PPF‐SO15‐DHTBT1 as emission polymers have maximum efficiencies LEmax = 7.0, 17.6 and 6.1 cd A−1 with CIE coordinates (0.15, 0.17), (0.37, 0.56) and (0.62, 0.36), respectively. 1D distributed feedback lasers using PPF‐SO30 as the gain medium are demonstrated, with a wavelength tuning range 467 to 487 nm and low pump energy thresholds (≥18 nJ). Blending different ratios of B (PPF‐SO), G (PPF‐SO‐BT) and R (PPF‐SO‐DHTBT) polymers allows highly efficient white polymer light‐emitting diodes (WPLEDs) to be realized. The optimized devices have an attractive color temperature close to 4700 K and an excellent color rendering index (CRI) ≥90. They are relatively stable, with the emission color remaining almost unchanged when the current densities increase from 20 to 260 mA cm−2. The use of these polymers enables WPLEDs with a superior trade‐off between device efficiency, CRI, and color stability.